What Motivates Software Crackers? - Goode, Sigi (Journal of business ethics, 2006)
Software piracy is a serious problem in the software industry. Software authors and publishing companies lose revenue when pirated software rather than legally purchased software is used. Policy developers are forced to invest time and money into restricting software piracy. Much of the published research literature focuses on software piracy by end-users. However, end-users are only able to copy software once the copy protection has been removed by a ‘cracker’. This research aims to explore why, if copy protection is so difficult to remove, do crackers invest their skill and time in this activity instead of more lucrative and legal employment. This study develops a framework of neutralisation, justification and motivation and goes directly to the initial software crackers to determine what motivates their activities. The study first applies this framework in an anonymous online survey of crackers. The study then conducts cognitive interviews with eight crackers to explore and further validate the survey’s findings. The study finds the challenge of removing the copy protection from software as the strongest motivation for the actions of crackers. Desire for social participation, while found to be rewarding, was considered unnecessary for crackers to continue their actions. Higher social status was not a motivational factor but was a perceived by-product of cracking. The study also raises areas for future research.